Exosome-based small RNA delivery: Progress and prospects - Mei Lu; Haonan Xing; Zhe Xun; Tianzhi Yang; Pingtian Ding; Cuifang Cai; Dongkai Wang; Xiaoyun Zhao (Elsevier, 2018)
RNA interfering (RNAi), mediated by small interfering RNAs and microRNAs, is currently one of the most promising tools of gene therapy. Small RNAs are capable of inducing specific post-transcriptional gene silencing, providing a potentially effective platform for the treatment of a wide array of diseases. However, similar to other nucleic acid-based drugs, the major hurdle of RNAi therapy is lack of efficient and non-immunogenic delivery vehicles. Currently, viruses, synthetic polymers, and lipid-based carriers are among the most widely studied vehicles for small RNA delivery. However, many drawbacks are reported to be associated with these delivery vehicles. There is a pressing need to replace them with more efficient and better-tolerated approaches. Exosomes secreted from the endocytic compartment of live cells, are a subtype of endogenous extracellular vesicles that transfer genetic and biochemical information among different cells, thus playing an important role in cell-cell communication. Recently, accumulating attention has been focused on harnessing exosomes as nanaocarriers for small RNAs delivery. Due to their natural role in shuttling endogenous nucleic acid in our body, exosomes may exhibit higher delivery efficiency, lower immunogenicity, and better compatibility than existing foreign RNA carriers. Importantly, exosomes own intrinsic homing capacity that can guide small RNAs across natural membranous barriers. Moreover, such a capacity can be further improved by adding appropriate targeting moieties. In this manuscript, we briefly review the progress and challenges of RNAi therapy, and discuss the potential of exosomes' applications in small RNA delivery with focus on the most recent advances in exosome-based small RNA delivery for disease therapy.